2021
DOI: 10.35848/1882-0786/ac039e
|View full text |Cite
|
Sign up to set email alerts
|

Channeled implantation of magnesium ions in gallium nitride for deep and low-damage doping

Abstract: Ion implantation into p-type gallium nitride (GaN) to a depth of several microns for power devices is a challenge because their activation is disturbed by the damage caused by implantation. To reduce this damage, a channeled implantation technique was applied to implant magnesium (Mg) ions into GaN (0001). Compared with random implantation, channeled implantation was demonstrated to implant and activate ions in >10 times deeper regions. Thus, the channeled implantation technique is indispensable for the dee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Recently, Nishimura et al reported the advantages of channeled implantation and confirmed the activation of the GaN using Cathode luminescence. 15,16) In addition, Matys et al fabricated and characterized GaN field-limiting rings (FLR) termination structures using Mg channel implanted layer. 11) However, there have been only a few reports of channeled implantation of Mg ions to GaN.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Nishimura et al reported the advantages of channeled implantation and confirmed the activation of the GaN using Cathode luminescence. 15,16) In addition, Matys et al fabricated and characterized GaN field-limiting rings (FLR) termination structures using Mg channel implanted layer. 11) However, there have been only a few reports of channeled implantation of Mg ions to GaN.…”
Section: Introductionmentioning
confidence: 99%
“…11) However, there have been only a few reports of channeled implantation of Mg ions to GaN. 11,[15][16][17] So far, we have evaluated the defects of GaN on sapphire induced by Mg random implantation using transmission electron microscopy (TEM), Raman spectroscopy and atomic force microscopy (AFM), 18) but the defects of Mg channel implanted layers have not been evaluated fully. In this work, we confirmed the activation of Mg and evaluated Mg channel implanted layers.…”
Section: Introductionmentioning
confidence: 99%
“…Ion beam irradiation is one of the promising and practical methods that can introduce defects and impurities into a material quantitatively and reproducibly [12,13]. For example, Ochedowski et al irradiated U ions as swift heavy ions to monolayer (1L)-graphene and molybdenum disulfide (MoS2) at different doses and investigated their effects on electrical properties [14].…”
Section: Introductionmentioning
confidence: 99%
“…As a non-UHPA approach, various Mg I/I techniques, such as channeling, high-temperature, and vacancy-guided implantation techniques, have been reported to suppress the introduction of defects. [17][18][19][20] However, as long as ions are implanted, annealing at temperatures lower than 1300 °C does not completely repair defects, and it seems difficult to fully activate Mg without UHPA. Thus, it is valuable to investigate Mg doping methods without Mg I/I.…”
mentioning
confidence: 99%